THE EFFECT OF IRRADIATION DOSE AND AMMONIA CONCENTRATION ON THE APPLICATION OF ELECTRON BEAM FOR TREATMENT GASES POLLUTION OF SO2AND NOX - Erizal Erizal (Universitas Gadjah Mada, 2007)
The application of electron beam for treatment gases pollution of SO2 and NOx has been studied. The simulated SO2 and NOx gases stream produced from diesel fuel burning boiler were flown into electron beam chamber. Irradiation was conducted using 1000 keV electron beam machine at the dose up to 8.8 kGy, while water vapour and the ammonia gas with variation concentration flew into the system during irradiation. The concentrations of the gases change were observed during processes. After evaluation, it was found that by increasing irradiation dose, the concentration of SO2 and NOx gases removal increases. The efficiency of gases removal may reach 98 % for SO2 and 88 % for NOX at a dose of 8.8 kGy. By increasing ammonia concentration, the efficiency gas removal increases. Besides, by-products from the irradiation yield were sulfate and nitrate salt compound which are possible to be used as a fertilizer.